2020
DOI: 10.21203/rs.3.rs-88850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety measures for COVID-19 do not compromise the outcomes of patients undergoing primary percutaneous coronary intervention: A single center study

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic impacting nearly 170 countries/regions and millions of patients worldwide. Patients with acute myocardial infarction (AMI) still need to be treated at percutaneous coronary intervention (PCI) centers with relevant safety measures. This study was conducted to assess the therapeutic outcomes of PCI performed under the safety measures and normal conditions. AMI patients undergoing PCI between January 24 to April 30, 2020 were performed under safety measures… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“… 40 , 41 One single-centre study reported a decline in hospitalizations with adult congenital heart disease (ACHD) during the pandemic, 42 and two studies demonstrated a significant increase in the incidence of stress cardiomyopathy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%
“… 40 , 41 One single-centre study reported a decline in hospitalizations with adult congenital heart disease (ACHD) during the pandemic, 42 and two studies demonstrated a significant increase in the incidence of stress cardiomyopathy. 43 , 44 …”
Section: Resultsmentioning
confidence: 99%